Weed interference periods in sesame crop - Lins,Hamurábi Anizio (2019)
ABSTRACT The sesame crop (Sesamum indicum L.) is sensitive to competition with weeds because of its low competitiveness that is directly linked to its slow initial growth. The control of weeds in the crop is an essential practice to ensure the high productivity of this oilseed. Therefore, to define the critical period of interference prevention is important to ensure efficiency and low control costs. Factors such as cultivar, environmental conditions, and cultivation system may alter the critical weed interference prevention period (CPWC). Therefore, the objective of this work was to determine the critical weed interference prevention period in two sesame cultivars. The critical weed interference prevention period for sesame cultivars, BRS Seda and CNPA G2, was defined in two years (2016 and 2017). Log-logistic regression of four parameters was used to determine the critical weed interference prevention period. The cultivar CNPA G2 was more competitive compared to the cultivar BRS Seda. The CPWC for BRS Seda was on average 67 and 52 days, whereas for CNPA G2 was 52 and 34 days, considering respectively, a loss of 5 and 10%. Weed control for BRS Seda and CNPA G2 should begin respectively between 12 and 15, and 17 and 20 days, considering a loss of 5 and 10%.